The Use of Tik Tok to Teach Speaking in Descriptive Text - Chalimah, Chalimah; Aldiansyah, Muhammad; Rakhmawati, Lilis; Din, Maaz Ud (STAI Miftahul Ula Nganjuk, 2024)
The English learning process in Indonesia is still experiencing difficulties, especially in the speaking aspect which is 22% % (Tambunsaribu & Yusniaty, 2021). The difficulty comes from the lack of teachers in providing interesting and interactive learning media. The purpose of this research was to determine the effectiveness of TikTok on students' speaking learning ability in the aspects of comprehension and fluency. This research method uses quantitative research with Mann-Whitney analysis test. The results of this research show that the class taught using TikTok has an average learning outcome of 22.18 while the class that is not taught using TikTok has an average learning outcome of 12.82. as a conclusion shows that TikTok is effective as a media for learning speaking especially in the aspects of comprehension and fluency. Keyword: Speaking, TikTok, Instructional Media